2007
DOI: 10.1111/j.1600-0560.2007.00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunolabeling pattern of cytokeratin 19 expression may distinguish sebaceous tumors from basal cell carcinomas

Abstract: CK 19 expression can be helpful in differentiating sebaceous tumors (including sebaceous adenomas, sebaceous epitheliomas and sebaceous carcinomas) from basal cell carcinomas and may be a useful adjunct when these entities are included in the differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…However, it is sometimes difficult to confirm sebocytic differentiation by only using the data from HE staining. Many reports on the immunohistochemical features of SC have been published, and detection of the following have been suggested to be useful for diagnosing SC or differentiating SC from other skin cancers: HMFG1 and HMFG2, BCA‐225, CA15‐3, CK8, carcinoembryonic antigen, epithelial membrane antigen (EMA), Thomsen–Friedenreich antigen and its precursor antigen, the androgen receptor (AR), CK15, adipophilin (ADP), perilipin, Ber‐EP4 and CK19 . Plaza et al .…”
Section: Sebaceous Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is sometimes difficult to confirm sebocytic differentiation by only using the data from HE staining. Many reports on the immunohistochemical features of SC have been published, and detection of the following have been suggested to be useful for diagnosing SC or differentiating SC from other skin cancers: HMFG1 and HMFG2, BCA‐225, CA15‐3, CK8, carcinoembryonic antigen, epithelial membrane antigen (EMA), Thomsen–Friedenreich antigen and its precursor antigen, the androgen receptor (AR), CK15, adipophilin (ADP), perilipin, Ber‐EP4 and CK19 . Plaza et al .…”
Section: Sebaceous Neoplasmsmentioning
confidence: 99%
“…Among them, CK7 showed the highest positive rate; 76% of ocular SC and 43% of extraocular SC showed a positive reaction with anti‐CK7 antibody. While the neoplastic cells of poorly differentiated SCC express CK7, most SCC do not express CK7. Therefore, immunohistochemical detection of CK7 in neoplastic cells may generally be useful for differentiating SC from SCC.…”
Section: Sebaceous Neoplasmsmentioning
confidence: 99%
“…Ishida et al showed that 14 (70%) BCC cases were positive for CK19 with focal staining pattern. However, Heyl and Mehregan reported that CK 19 was strong, diffusely positive in 9/14 (64%) of their studied cases. In Bedir et al study, 22(88%) of the BCC cases showed positive staining for CK19 mostly with diffuse staining pattern; while 3 (30%) TEs cases showed positive staining for CK19 mostly with a focal pattern.…”
Section: Discussionmentioning
confidence: 73%
“…In our case, the signal intensity resonance imaging examination resembled that of any benign EAC mass. Because the clinical and histologic difference of sebaceoma from sebaceous adenoma or malignant sebaceous carcinoma may be difficult, subtle, and not well defined, some authors (1,4) have proposed the use of immunohistochemical antibodies against epithelial membrane antigen or enzyme proteinase K or cytokeratin 19.…”
Section: Discussionmentioning
confidence: 99%
“…Sebaceoma can be solitary or may be multiple and associated with multiple adenomatous polyps and sebaceous tumor (Muir-Torre syndrome) so that an accurate clinical evaluation should be performed (1,4).…”
Section: Discussionmentioning
confidence: 99%